2011
DOI: 10.15666/aeer/0903_253264
|View full text |Cite
|
Sign up to set email alerts
|

Lantana Camara L. Invasion and Impact on Herb Layer Diversity and Soil Properties in a Dry Deciduous Forest of India

Abstract: Abstract. Invasion of lantana (Lantana camara L.) in dry deciduous forest is capable of causing changes in micro sites (soil properties and species composition) in which they invade. As lantana is most conspicuous invader in the Vindhyan dry deciduous forests of India. We analyzed the effect of this invasive species on the composition of herbaceous layer and on soil properties. Habitats with different level of canopy cover were analyzed. And the canopy cover was significantly related to the lantana cover. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
6
11
0
Order By: Relevance
“…The increased pH from all the highly invaded sites and even from the moderately invaded sites were found to have a strong positive correlation with the coverage and total shrub density (r= 0.89). The similar change had been recorded from a dry deciduous forest of India (Sharma and Raghubanshi, 2011). All the moderate and highly invaded areas showed the elevation in soil macronutrients including N, P, K, Ca, Mg, Mn, and took up about twice as much of these macronutrients per unit area as the native plants.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The increased pH from all the highly invaded sites and even from the moderately invaded sites were found to have a strong positive correlation with the coverage and total shrub density (r= 0.89). The similar change had been recorded from a dry deciduous forest of India (Sharma and Raghubanshi, 2011). All the moderate and highly invaded areas showed the elevation in soil macronutrients including N, P, K, Ca, Mg, Mn, and took up about twice as much of these macronutrients per unit area as the native plants.…”
Section: Discussionsupporting
confidence: 78%
“…In forest habitat the height of the shrub was found unexpectedly higher than other habitats, this was explained due to the enormous power of Lantana to compete with the native species for natural resources like sunlight, as Lantana is a photophilous (growing best in strong light) plant, and in closed canopy forest areas it competes with the native trees in order to get more sunlight, this finding was also supported by the earlier study conducted by Sharma and Raghubanshi (2011). Both SOC (%) and total N (%) showed very strong positive correlation while taken as a variable to measure the crown diameter of Lantana (r=0.94) and (r=0.98) respectively.…”
Section: Discussionsupporting
confidence: 67%
“…Lantana invasion in different areas is a much more recent phenomenon and is reducing species richness of native understory species while also causing compositional changes in the herbs and shrubs, as well as tree seedlings (Sharma and Raghubanshi 2010;Sharma and Raghubanshi 2011). Nevertheless its enormous potential to be an abundant fuel source and sequester CO 2 from the atmosphere should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that invasive species are the second biggest cause of species extinction, behind habitat destruction (Sharma & Raghubanshi, 2011). In particular, the threat of invasive species to the environment of small islands is worse than that of large land masses (Glen et al, 2013) because small islands have a low biological resistance to invasive species.…”
Section: Introductionmentioning
confidence: 99%